Pentateuch and Pedagogy: An Introduction - Leonard-Fleckman, Mahri (Teaching theology and religion, 2025)
This piece is an introduction to the collection of papers presented at the Society of Biblical Literature 2024 “Pentateuch and Pedagogy” session. The session was co-chaired by the Pentateuch and the Historiography and the Hebrew Bible program units. We explain the rationale behind the session, its organization and aims, and the three key issues we wished to highlight among the respondents. We conclude by drawing attention to a few themes that emerged in the session and that we consider to chart a positive path forward for teaching the Pentateuch in diverse institutional contexts.